2015
DOI: 10.1371/journal.pone.0116674
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content and Root Color of Cultivated Carrot: A Candidate-Gene Association Study Using an Original Broad Unstructured Population

Abstract: Accumulated in large amounts in carrot, carotenoids are an important product quality attribute and therefore a major breeding trait. However, the knowledge of carotenoid accumulation genetic control in this root vegetable is still limited. In order to identify the genetic variants linked to this character, we performed an association mapping study with a candidate gene approach. We developed an original unstructured population with a broad genetic basis to avoid the pitfall of false positive detection due to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 66 publications
(83 reference statements)
10
31
2
Order By: Relevance
“…Previous studies in carrot have mapped QTL for carotenoid accumulation with AFLP markers ( Santos and Simon 2002 ), and/or have utilized candidate genes from the MEP and carotenoid biosynthetic pathways to identify the genetic control of β-carotene accumulation ( Just et al 2007 , 2009 ; Jourdan et al 2015 ; Iorizzo et al 2016 ). However, this is the first study to use a whole-genome approach along with a transcriptome analysis to better understand the regulation of high β-carotene accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in carrot have mapped QTL for carotenoid accumulation with AFLP markers ( Santos and Simon 2002 ), and/or have utilized candidate genes from the MEP and carotenoid biosynthetic pathways to identify the genetic control of β-carotene accumulation ( Just et al 2007 , 2009 ; Jourdan et al 2015 ; Iorizzo et al 2016 ). However, this is the first study to use a whole-genome approach along with a transcriptome analysis to better understand the regulation of high β-carotene accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several carrot studies have found associations between carotenoid content and carotenoid biosynthetic genes, including a study by Arango et al (2014) , which identified a Carotene Hydroxylase ( CYP97A3 ) homolog that contributed to increased carotenoid content due to increased amounts of α-carotene. Further, a candidate gene association analysis by Jourdan et al (2015) suggested total carotenoid and β-carotene quantities were significantly associated with the genes Zeaxanthin Epoxidase ( ZEP ), Phytoene Desaturase ( PDS ), and Carotenoid Isomerase ( CRTISO ). To verify whether these genes underlie the Y 2 locus, a whole-genome integrative approach was used.…”
mentioning
confidence: 99%
“…Quantitative trait locus (QTL) analyses have demonstrated that significant levels of natural variation for seed carotenoid traits exist in several plant species (Wong et al, 2004;Abbo et al, 2005;Fernandez et al, 2008;Blanco et al, 2011;Kandianis et al, 2013), but these intervals typically contain hundreds or thousands of genes; as a result, few causal loci underlying QTLs have been defined (Pozniak et al, 2007;Chandler et al, 2013;Gonzalez-Jorge et al, 2013). Significant natural variation for seed carotenoids also is present in diversity panels of maize (Zea mays), wheat (Triticum aestivum), Citrus spp., chickpea (Cicer arietinum), carrot (Daucus carota), pea (Pisum sativum), cassava (Manihot esculenta), and Arabidopsis (Abbo et al, 2010;Arango et al, 2010;Welsch et al, 2010;Yan et al, 2010;Blanco et al, 2011;Cook et al, 2012;Gonzalez-Jorge et al, 2013;Kandianis et al, 2013;Owens et al, 2014;Jourdan et al, 2015;Suwarno et al, 2015). Advances in high-throughput phenotyping and genotyping are allowing some of the genes underlying this natural variation to be identified through genome-wide association studies (GWAS; Harjes et al, 2008;Zhou et al, 2012;Gonzalez-Jorge et al, 2013;Owens et al, 2014;Wen et al, 2014;Sonah et al, 2015).…”
mentioning
confidence: 99%
“…Golden Rice was further enhanced by introducing a different phytoene synthase gene and increasing b-carotene accumulation another ten-fold [142]. Combined quantitative genetic and metabolomic approaches have recently identified several QTLs associated with b-carotene accumulation and/or carotenoid composition in maize [143], potato [144], carrot [145] and tomato [146], as well as candidate genes that could provide useful targets in carotenoid (e.g. b-carotene and lycopene) biofortification efforts.…”
Section: Nutraceuticals Biofortification and Metabolomicsmentioning
confidence: 99%